2019
DOI: 10.1097/md.0000000000014854
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of povidone-iodine suppository before transrectal ultrasonography-guided prostate biopsy

Abstract: Objectives: To investigate a way to reduce infectious complication after transrectal ultrasonography-guided prostate biopsy (TRUS-Bx), we planned a randomized trial to determine whether the use of the povidone-iodine suppository is effective in preventing infectious complications. Methods: This study prospectively assessed 250 patients who underwent TRUS-Bx during December 2014 and May 2016. Clinical questionnaire responses and safety were evaluated. Povidone-iodine sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
2
3
0
Order By: Relevance
“…with a similar protocol of parenteral cephalosporin for prophylaxis had no infections with povidone-iodine rectal suppository. [ 25 26 27 ] In contrast, our study protocol showed a 2.3% infection rate in Group P. Our study corroborates literature justifying the use of intrarectal povidone-iodine over formalin disinfection of needles for TRUSPB. [ 14 ] Rate of hospitalization in the current study ( n = 8, 1.3%) was comparable with another reported series, which had 1.9% admission rates and like our study, reported no mortality.…”
Section: Discussionsupporting
confidence: 86%
“…with a similar protocol of parenteral cephalosporin for prophylaxis had no infections with povidone-iodine rectal suppository. [ 25 26 27 ] In contrast, our study protocol showed a 2.3% infection rate in Group P. Our study corroborates literature justifying the use of intrarectal povidone-iodine over formalin disinfection of needles for TRUSPB. [ 14 ] Rate of hospitalization in the current study ( n = 8, 1.3%) was comparable with another reported series, which had 1.9% admission rates and like our study, reported no mortality.…”
Section: Discussionsupporting
confidence: 86%
“…These studies support the ndings in our study that transrectal povidone-iodine application reduces the incidence of post-biopsy infectious complications [24,25,28]. However, Ryu et al [29] observed no reduction in post-biopsy infectious complication rates following the application of transrectal povidoneiodine, contrary to the ndings of previous studies, including ours.…”
Section: Discussionsupporting
confidence: 85%
“…Five RCTs used ciprofloxacin, levofloxacin, or ofloxacin as AP [ 2 , 5 , 7 , 8 , 17 ]. Only one study, conducted by Rye et al, used ceftriaxone administered intravenously at a single dose of 2 g [ 6 ]. There were 1399 patients in the PI plus AP group and 1475 patients in the AP monotherapy group.…”
Section: Evidence Synthesismentioning
confidence: 99%